Leo Smith : a biographical sketch - McCarthy, Pearl (University of Toronto Press, 2017)
LEO SMITH-cellist, journalist, composer, and teacher-was one of the most picturesque and frequently idolized artists on the Canadian scene. Pearl McCarthy's biography vividly recapitulates the Canadian musical scene between 1910 and 1952 and provides a coda to the career of an important influecne in Canadian music.